Magnetic nanomaterials as an effective absorbent material for removal of fluoride concentration in water: a review - Sallahuddin Panhwar; Hareef Ahmed Keerio; Nadar Hussain Khokhar; Muhammad Muqeet; Zouhaib Ali; Muhammad Bilal; Ajeeb Ul Rehman (IWA Publishing, 2024)
The rapid increases in industrialization and populations are significant sources of water contamination. The speed with which contamination of groundwater and surface water occurs is becoming a serious problem and poses a significant obstacle for water stakeholders. Heavy metals, organic, and inorganic contaminants in the form of suspended and dissolved materials are just a few of the contaminants that can be found in drinking water. One of the most common contaminants in the water is fluoride, which is responsible for numerous toxic diseases. Different traditional techniques, for example, coagulation, ion exchange, absorption, and membrane filtration are being used to dispose of fluoride from water. However, nanomaterials such as magnetic nanoparticles (NPs) are very efficient, reliable, cost-effective, and stable materials to replace traditional water treatment techniques. There has been an increase in interest in the application of nanomaterials to the purification of drinking water over the past few decades. The use of magnetic NPs, such as metal and metal oxide NPs, to remove fluoride ions and organic matter from water is highlighted in this review article. Also, this section also discusses the properties, benefits and drawbacks, and difficulties of utilizing magnetic NPs in the process of purifying drinking water. HIGHLIGHTS Fluoride is a common contaminant in water, which is responsible for numerous toxic diseases.; Coagulation, ion exchange, absorption, and membrane filtrations are being used to dispose of fluoride from water.; Magnetic nanoparticles are very efficient, reliable, cost-effective, and stable materials to replace traditional water treatment techniques.;